Computational Approach to Evaluate Eugenol Affinity and Derivatives Empirical Against Cu(II) - Muhammad Cholid Djunaidi; Tantri Nevi Astuti; Parsaoran Siahaan (Molekul, 2019)
A computational approach to assess the emperical results of eugenol affinity, eugenoxy acetate (EOA), and pyridine methyl eugenoxy acetate (PMEOA) against Cu2+has been done. This research aims to determine the effects of the functional groups (−OH, −COOH, and −N) on eugenol and their derivatives on the selectivity of Cu2+adsorption experimentally and to calculate the energy interaction between eugenol compounds and derivatives with Cu2+. The experimental approach was carried out by solvent extraction method, using 10 mL of Cu2+10 ppm solution along with 0.3089 mmol of eugenol, EOA and PMEOA. The remaining concentration of Cu2+metal after extraction in the water phase was measured using an Atomic Absorption Spectrophotometer (AAS). Assessments of the Cu2+metal interaction with eugenol, EOA and PMEOA compounds were carried out using the ab initio method with 6-31G** basis set to predict the interaction energy. The results showed that pyridine methyl eugenoxy acetate (PMEOA) can separate Cu2+better than eugenol and EOA with extraction efficiency (% E) = 78.76%. The calculation results of Cu2+metal interactions with eugenol, EOA, and PMEOA compounds found that PMEOA has the lowest energy of interaction compared to eugenol and EOA with Cu2+metal.